Traditional v. modern dietary patterns among a population in western Austria: associations with body composition and nutrient profile. Issue 3 (29th November 2018) - Egg, Sabrina; Erler, Judith; Perktold, Bernhard; Hasenegger, Verena; Rust, Petra; Ramoner, Reinhold; König, Jürgen; Purtscher, Anna Elisabeth
Abstract: Objective: The present study aimed to identify dietary patterns, compare dietary patterns regarding nutrient profile and investigate the association between dietary patterns and body composition in a population in western Austria. Design: In a cross-sectional study, eating habits, anthropometric measurements and body composition were assessed. Food intake was collected by two non-consecutive 24 h recalls. Factor analysis (principal component analysis) with complementary cluster analysis was applied to identify dietary patterns. Associations of dietary patterns with body composition and nutrient profile were examined by the t test, one-way ANOVA and ANCOVA with Bonferroni's correction. The χ 2 test was used for categorical variables. Setting: Tyrol, western Austria, 2014–2015. Participants: Adults ( n 463) aged 18–64 years. Results: Three dietary patterns were derived, labelled as the 'health-conscious', the 'western' and the 'traditional' dietary pattern. After adjustment for confounding variables, individuals following the traditional and western patterns were more likely to be overweight/obese ( P <0·001) and to have a higher body fat percentage ( P <0·05). Individuals following the traditional dietary pattern consumed significantly more SFA and less PUFA and dietary fibre ( P <0·001) than those in the other groups. Conclusions: Individuals who mostly eat in a traditional way should be encouraged to increase their consumption of vegetables, fruits, whole grains and healthy fats. It is important to know local eating habits not only for planning individual nutritional therapy, but also for well-directed public health actions.